Analisis Kinerja Guru IPS SMP Bersertifikat Pendidik di Kota Metro Tahun Ajaran 2017/2018 - Aganta Muliantami; Sumadi Sumadi; Sugeng Widodo (JPG (Jurnal Penelitian Geografi), 2019)
This study aims to find out : (1) the ability to design a lesson plan, (2) the ability to carry out learning, (3) the ability to evaluate the learning of social studies teachers at public and private middle schools in Metro City academic year 2017/2018. This research use a descriptive method. This study is a simple randomize taken by drawing, taking a sample of 50% of 41 social studies teachers. The data collection is done by using questionnaire techniques, documentation, interviews, and observations. The data analysis technique used is percentages. The results of the study show the teacher's performance possessed by social studies teachers with the following indicators: (1) social studies teachers already have the ability to design the learning plan well as much as 36.58%, (2) social studies teachers have the ability to carry out learning with sufficient criteria as much as 36.58%, ( 3) social studies teachers have the ability to evaluate the learning with sufficient criteria as much as 36.58%.Penelitian ini bertujuan untuk : (1) kemampuan merencanakan pembelajaran, (2) kemampuan melaksanakan pembelajaran, (3) kemampuan mengevaluasi pembelajaran guru IPS pada SMP Negeri dan Swasta di Kota Metro Tahun Ajaran 2017/2018. Penelitian ini menggunakan metode deskriptif. Penelitian ini menggunakan random sederhana diambil secara undian, pengambilan sampel sebanyak 50% yaitu 41 guru IPS. Pengumpulan data dilakukan dengan teknik kuesioner, dokumentasi, wawancara dan observasi. Teknik analisis data menggunakan presentase. Hasil penelitian menunjukkan kinerja guru yang dimiliki oleh guru IPS dengan indikator sebagai berikut: (1) guru IPS sudah memiliki kemampuan merencanakan pembelajaran dengan baik sebanyak 36,58%, (2) guru IPS memiliki kemampuan melaksanakan pembelajaran dengan kriteria cukup sebanyak 36,58%, (3) guru IPS memiliki kemampuan mengevaluasi pembelajaran dengan kriteria cukup sebanyak 36,58%.Kata Kunci: analisis, guru IPS, kinerja